Naviguer dans des grands arbres avec ControlTree - Caroline Appert; Jean-Daniel Fekete (IHM'07: Proceedings of the International Conference on Association Francophone d'Interaction Homme-Machine, 2007)
This article presents ControlTree, a relevant technique to select a node is a very large node-link representation using a continuous interaction. The node-link representation is dynamic and driven by the cursor location to optimize screen space and to ease the selections. ControlTree uses a snapping mechanism and adapts the OrthoZoom technique to offer an alternative to common "point-and-click" techniques. We also present a preliminary theoretical evaluation showing that ControlTree is a promising technique.